ДОСЛІДЖЕННЯ З ЕКСПЕРИМЕНТАЛЬНОГО ВПРОВАДЖЕННЯ ЕЛЕКТРОННИХ РЕЦЕПТІВ В УКРАЇНІ - Парновський, Б. Л.; Заліська, О. М.; Бойко, А. І. (Фармацевтичний часопис, 2015)
In 1979 B.L.Parnovskyy and colleagues elaborated a technique to prepare recipes for automated processing that was encoded: (No) medical hospitals, age and sex of the patient, physician specialty, code preparations (state) and code dosage forms, the type of recipe (manufacture or extemporaneous medicines). The system is modeled by specifying in the aggregate 995 prescriptions for drugs are prepared using a computer. Experience of leading countries suggests the pharmacoeconomic benefits of e-prescribe of medicines, when using by the Internet accurately, without errors and clear hard copy prescription issued by a physician is transferred directly to the pharmacy. In 2006 set the standard requirements for electronic prescriptions in approving instruction and dispensing of electronic prescriptions respectively in 2009. According to the literature the electronic system of e-prescription medicine allows doctors to choose lower cost substitute for generics, saving 845000 US $ per 100000 patients a year. Taking into account their own and International Studies in 2011, the concept of implementing e-prescription in Ukraineto prevent negative side effects of drugs, while the application of computer technologies. We have elaborated the ways of transforming pharmaceutical information in pharmaceutical knowledge database using electronic prescriptions. The results of theoretical studies, taking into account the factor of prevention of unwanted interactions of medicines were argue for differentiated methods of computer processing recipes for prepared medications and prescriptions for extemporaneous medicines. Allowing accounted for consumption and the need for their active pharmaceutical ingredients and excipients. The experiment of organizational and methodological support to obtain diagnostic and pharmaceutical pharmacy of extemporaneous prescriptions was launched in 2014 [9]. We have processed information provision and discharge algorithm electronic prescriptions in accordance with all requirements of the existing order of the Ministry of Health ofUkraine of 19.07.2005 № 360. We have modeled computer database "Reception and analysis of extemporaneous prescriptions" and "Information support operations process manufacturing extemporaneous medicines" with information and regulatory functions in relation to prescribing extemporaneous prescriptions and production of drugs in pharmacies serving the hospital and ambulatory patients [16]. We have introduced electronic prescriptions for example of ready medications for diabetes treatment, an experiment was conducted in Ternopil region, for extemporaneous formulations - in Lviv region, we had got the implementing acts. In our opinion, due to the reform of the pharmaceutical providing in health care ofUkraine is needed a phased transition to modern electronic prescribes and e-prescriptions. The experience shows that electronic prescriptions promote adequate prescription of drugs prescribed by doctors with regard to prevention of undesirable interactions, control accounting and a determine the need for medicines.